Uranium deposition in bones of wistar rats associated with skeleton development - Rodrigues, G.; Arruda-Neto, J. D T; Pereira, R. M R; Kleeb, S. R.; Geraldo, L. P.; Primi, M. C.; Takayama, L.; Rodrigues, T. E.; Cavalcante, G. T.; Genofre, G. C.; Semmler, R.; Nogueira, G. P. [UNESP]; et al. (Elsevier, 2013)
Sixty female Wistar rats were submitted to a daily intake of ration doped with uranium from weaning to adulthood. Uranium in bone was quantified by the SSNTD (solid state nuclear track detection) technique, and bone mineral density (BMD) analysis performed. Uranium concentration as a function of age exhibited a sharp rise during the first week of the experiment and a drastic drop of 70% in the following weeks. Data interpretation indicates that uranium mimics calcium. Results from BMD suggest that radiation emitted by the incorporated Uranium could induce death of bone cells. © 2013 Elsevier Ltd.
Keywords: Bone mineral density; Radiobiological effects; Skeleton bones; Uranium incorporation; Wistar rats; Daily intake; Data interpretation; Female Wistar rats; Solid-state nuclear track detections; Uranium concentration; Wistar rat; Bone; Data processing; Musculoskeletal system; Uranium; uranyl nitrate; age; animal experiment; animal tissue; bioaccumulation; bone density; bone development; controlled study; female; femur; nonhuman; priority journal; quantitative analysis; rat; teratogenesis